1997
DOI: 10.1093/rheumatology/36.6.677
|View full text |Cite
|
Sign up to set email alerts
|

Lung findings on high-resolution computed tomography in idiopathic ankylosing spondylitis--correlation with clinical findings, pulmonary function testing and plain radiography

Abstract: Previous studies on the association of ankylosing spondylitis and abnormalities of the lung parenchyma have been based largely on plain radiography and pulmonary function testing. This study, although uncontrolled, is the first to use high-resolution computed tomography to examine the entire lung parenchyma in ankylosing spondylitis patients, and to correlate the findings with clinical assessment, plain radiography and pulmonary function testing. The study population comprised 26 patients meeting the New York … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
2
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 0 publications
2
27
2
4
Order By: Relevance
“…In contrast to our study, they did not find any correlation between PFT and thoracic expansion. Casserly et al (1997) reported that the patients who had PFT abnormality shown abnormal HRCT changes and there was a statistically significant correlation with HRCT and PFT findings.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to our study, they did not find any correlation between PFT and thoracic expansion. Casserly et al (1997) reported that the patients who had PFT abnormality shown abnormal HRCT changes and there was a statistically significant correlation with HRCT and PFT findings.…”
Section: Discussionmentioning
confidence: 94%
“…Fundamental changes are apical fibrobullous changes, interstitial lung disease, pleural thickening, and effusion [2,3]. The thoracal movements may be restricted due to the involvement of the thoracic, costovertebral, manubriosternal and costosternal vertebrae, and the effect of postural factors along with the sacroiliac joint involvement, sometimes lead to restrictive respiratory distress [4].…”
Section: Introductionmentioning
confidence: 99%
“…In clinical applications, the chest expansion measurement, costochondral joint tenderness, chest X-ray, carbon monoxide diffusion capacity, lung function tests, bronchoalveolar lavage, high-resolution tomography of the lung and transbronchial biopsy all can be used to assess the respiratory system involvement in patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Considering that there is no definitive treatment for AS and the main goals are to educate and make patient aware of his/her participation in an exercise program so that he/she can keep a functional posture and also maintain movements, this research is a transversal study aiming at comparing patients with AS and verifying the effect of moderate regular physical activity in these patients' respiratory capacity. [4][5][6][7][8] …”
Section: Introductionmentioning
confidence: 99%